EKSISTENSI PASAR MODAL PERBANKAN SYARI`AH DI INDONESIA DALAM MENGHADAPI PASAR BEBAS DI ERA GLOBALISASI - APRILIAN JANI, TRI Aprilian (Jurnal Akuntansi AKUNESA, 2013)
Globalization is a form of interaction of the dependence and interrelation betweencountries which has a led competition, it would be affected the economy existenceof a country`s. Whereas, the capital market of Islamic banking is a part offinancial markets which the capital market of Islamic banking has a competitionto face of free market between countries in the era of globalization. The purposeof the study is finding out of the existence of the Islamic banking capital market inIndonesian to face of free markets in the era of globalization.Keywords : globalization, free markets, capital market, Islamic banking